2002
DOI: 10.1177/088307380201700606
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome Following Stroke in Children

Abstract: The aim of this study was to describe the functional consequences of childhood stroke in terms of activity limitation and to explore the relationship between extent of brain damage, impairment, and functional sequelae. A further aim was to describe the health of the parents of these children. Seventeen children and adolescents with cerebral infarction in the territory of the middle cerebral artery were enrolled in the study. A new activity limitation measure with a 4-point Likert scale (the Paediatric Stroke A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
123
3
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 21 publications
10
123
3
2
Order By: Relevance
“…[7][8][9][10] However, younger age at stroke is associated with poorer intellectual outcome and a broader spectrum of dysfunctions across multiple neuropsychological domains. 6,[11][12][13][14][15][16][17] Further, children with combined cortical and subcortical lesions have overall poorer cognitive outcome, 16,18 and larger lesion size negatively influences cognitive and functional outcome, 4,19,20 possibly due to disruption of more neural network connections, adversely affecting functional brain organization. 21 Regarding lesion laterality, controversial reports exist concerning the effect of lesion laterality on neuropsychological outcome.…”
mentioning
confidence: 99%
“…[7][8][9][10] However, younger age at stroke is associated with poorer intellectual outcome and a broader spectrum of dysfunctions across multiple neuropsychological domains. 6,[11][12][13][14][15][16][17] Further, children with combined cortical and subcortical lesions have overall poorer cognitive outcome, 16,18 and larger lesion size negatively influences cognitive and functional outcome, 4,19,20 possibly due to disruption of more neural network connections, adversely affecting functional brain organization. 21 Regarding lesion laterality, controversial reports exist concerning the effect of lesion laterality on neuropsychological outcome.…”
mentioning
confidence: 99%
“…This finding is in contrast to previous studies, which showed that combined cortical and subcortical lesions are significantly more likely to result in cognitive impairment in the long term compared to isolated cortical or subcortical infarctions 18,19 . One study even associated the presence of isolated subcortical lesions with a favorable outcome 20 . Although the study criteria could explain these differences, the leading cause of these results may lie in the size of the stroke, since combined lesions are likely to be the largest, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Motor impairment is common and health-related quality of life significantly affected in these children. 4 Although effective rehabilitation has the potential to improve this, scarcity of resources means these children have minimal input beyond the acute phase of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive CIT is effective in acute rehabilitation of adult stroke patients. 2,3 As hand function is the most disabling aspect of motor impairment after paediatric AIS 1,4 we were interested in the potential benefits of CIT in this group. The current pilot study aims to investigate the feasibility, tolerability, and effect of mCIT in school-aged children with hemiparesis after AIS.…”
mentioning
confidence: 99%